UPAYA PENEGAKAN HUKUM TERHADAP PENYALAHGUNAAN NARKOTIKA DAN OBAT-OBATAN TERLARANG DI KABUPATEN DAIRI - Matondang, Cyntia Theresia; Sitanggang, Welson; Siagian, Sofia; Fadil, Muhammad (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The aim of the study was to analyze the factors that influence the community as perpetrators of narcotics attacks in the Dairi district. To find out, explain and analyze law enforcement against perpetrators of narcotics crimes. Research results: Factors that influence the people of Dairi Regency as perpetrators of narcotics threats are legal substance, legal structure, facilities, legal culture and environment. The most influential factor is internal to them. Law enforcement against perpetrators of narcotic narcotics crimes committed in the community can be said to be classified as effective. Suggestion: Pay attention to the people of the Dairi district about the impact of drugs on the community. By conducting counseling for the people of the Dairi district. And also parents can give directions from an early age about giving more attention to children so that they have good life principles and morality so they are not easily influenced by doing things that break the law. Especially for Judges to carry out diversion against Communities who commit criminal acts so that it has a good impact on the Pandanggan community who are in conflict with the law.